Hematological and Neurotoxic Effects of Endosulfan Pesticide on Common Carp Cyprinus carpio: Abdulmotalib J.Al-Rudainy and Mohhamed H.Kadhim - Al-Rudainy, Abdulmotalib J. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study including determined blood picture by measuring red blood cells count, hemoglobin concentration, packed cell volume and white blood cells in common carp Cyprinus carpio, as well as description behavior and growth of carp fish .In order to estimate LC50 used 240 fingerlings of common carp Cyprinus carpio were exposed to 0.0008μg/L, 0.0010μg/L, 0.0011μg/L, 0.0012μg/L, 0.0013μg/L, 0.0014μg/L and 0.0015μg/L. The LC50 of endosulfan was 0.0012μg/L for 48h of exposure Fish behavioral were recorded that showed abnormalities after exposure to the various endosulfan concentrations such as increase swimming activity, hypersensitivity, jerky movement, violent movements, loss of equilibrium, hyperactivity, increase operculum movement, frequent jumping, swimming at the water surface, erratic swimming, spiraling, convulsion, escape attempts from the aquarium with respiratory stress and decrease in respiratory rate as well as a significant decrease at (P<0.05) in body weight of all treated groups. The result of blood picture showed a significant reduction in red blood cells count, hemoglobin concentration, packed cell volume values while the number of white blood cells was showed a significant increase in its values.